Impulse zur Überarbeitung mathematischer Schülertexte und ihre Auswirkungen (mathematica didactica, 2004)
In the beginning many students have difficulties when asked to write a mathematical text. In this article examples of sixth-graders are presented to show how hints from the teacher can on the one hand help students to write and revise their mathematical texts and on the other hand divert them from their own good ideas. When the revision was guided by individual written questions from the teacher, most students. texts gained.